104. Combined CBSST and Oxytocin for Social Function in People With Schizophrenia - Buchanan, Robert (Schizophr Bull, 2017)
Background: A significant proportion of people with schizophrenia are characterized by impaired ability to socially engage with others, which may reflect social aversion secondary to defeatist beliefs; decreased motivation for social interactions; and/or impairment in the normal reinforcement value of social interactions. Unfortunately, pharmacological interventions have limited benefits for impaired social function, whereas psychosocial interventions provide only partial benefit for this critical aspect of the illness. The development of an effective intervention for functional outcomes remains a central therapeutic challenge. The current study assessed whether the addition of intranasal oxytocin to Cognitive Behavioral Social Skills Training (CBSST) improved social function. Methods: Participants with DSM-IV-TR schizophrenia or schizoaffective disorder entered a 24-week, double-blind, placebo-controlled, randomized clinical trial with a 3-month follow-up evaluation. The study was conducted at two sites: Maryland and California. Participants were randomized to either: intranasal oxytocin 36 I.U. (3 sprays) BID (n = 31) or intranasal placebo-oxytocin 3 sprays BID (n = 31). All participants received CBSST, which was delivered in four 6-session modules (cognitive, social, and problem-solving CBSST modules plus a module adapted from Social Cognition and Interaction Training). The modules were delivered twice in biweekly 1-hour sessions, for a total of 48 sessions over 24 weeks. Birchwood Social Functioning Scale (SFS) was used to assess social function; the Defeatist Performance Attitude Scale (DPAS) was used to assess defeatist beliefs; the Asocial Beliefs Scale (ABS) was used to assess social disinterest and aversion; and the Scale for the Assessment of Negative Symptoms (SANS) total score was used to assess negative symptoms. Results: In the intent-to-treat analyses, there were no significant group differences in the SFS total score (Treatment × Week interaction: F = 0.96; df = 2, 40; P = .39) or ABS total score (Treatment × Week interaction: F = .12; df = 2, 39.7; P = .89). There was a trend for a significant reduction in defeatist beliefs among the participants randomized to oxytocin (Treatment × Week interaction: F = 2.86; df = 2, 67.2; P = .07). There were no significant group differences in SANS total score (Treatment × Week interaction: F = 0.96; df = 6, 39.7; P = 0.46), though the interpretation of the effect of oxytocin on SANS total score was complicated by the presence of a significant site effect: there was a significant placebo effect at the California site, which was markedly greater in magnitude than the observed oxytocin effect for these symptoms. Conclusion: The results of the intent-to-treat analyses provide minimal support for the utility of add-on intranasal oxytocin to CBSST for improvement in social function. Oxytocin was associated with trend improvement in defeatist attitudes and greater reduction in negative symptoms at one of the two study sites. (clinicaltrials.gov, trial number: NCT01752712)